PERANCANGAN PAKAIAN READY-TO-WEAR WANITA DEWASA MUDA MENGGUNAKAN KAIN JOGAKBO UNTUK BRAND VIRA PUSPITA - Virania Puspita Sari (Universitas Ciputra Surabaya, 2019)
“ DESIGNING READY TO WEAR CLOTHING FOR YOUNG ADULT WOMAN USING JOGAKBO FOR THE VIRA PUSPITA BRAND” K-pop phenomenon or hallyu wave in Indonesia had grown in significant pace since 2000. This affects Indonesian’s youth on many aspects, especially in fashion. This could be proven due to a lot of designs bears resemblance to Korean’s design themes, such as Korean patchwork or jogakbo. Jogakbo is a form of traditional patchwork from Korea which is usually used by Koreans as a wrapper for various objects or a form of clothing. Nowadays at the moment, Jogakbo is re-introduced/ re-invented in fashion world as a wearable art which the patchwork was made as if it is an art. By analyzing the market demand in Indonesia, which is quite large, Vira Puspita brand decided to take on jogakbo as a main concept which will be presented in ready to wear collection for fall/winter 2018/2019. With the main purpose of introducing jogakbo to Indonesians as well as a media to give it appreciation towards Indonesia’s art and culture.